Estimating the Price Elasticity of Residential Water Demand: The Case of Phoenix, Arizona. (9th February 2014) - Yoo, James; Simonit, Silvio; Kinzig, Ann P.; Perrings, Charles
Abstract: Changes in water availability, and hence price, are expected to be amongst the most disruptive effects of climate change in many parts of the world. Understanding the capacity of society or consumers to adapt to such changes requires understanding the responsiveness of water demand to price changes. We estimate the price elasticity of residential water demand in Phoenix, Arizona, which is likely to be strongly impacted by climate change. Most existing approaches to the estimation of water demand functions have limited capacity to isolate the effect of price on water consumption where there is little variation in water price. A recent study by Klaiber et al. (2012) attempts to address this issue by using differences in consumption levels, and weather‐related characteristics to isolate the price effect on water demand, and by using a constant term in a differenced regression model. We also estimate a differenced regression model, but include direct measures of changes in water prices. This inclusion successfully isolates the price effect on water demand, and enables us to distinguish between the short‐ and long‐run price elasticity of water demand, and hence the short‐and long‐run adaptation to changes in water availability.